2011
DOI: 10.2174/1874357901105010012
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Interaction of the Hepatitis Delta Virus Small Antigen with the ELAV-Like Protein HuR

Abstract: The small and large delta antigens (S-HDAg and L-HDAg, respectively) represent two forms of the only protein encoded by the hepatitis delta virus (HDV) RNA genome. Consequently, HDV relies, at a large extent, on the host cell machinery for replication and transcription. Until now, only a limited number of cellular proteins were identified as S-HDAg or L-HDAg partners being involved in the modulation of the virus life cycle. In an attempt to identify cellular S-HDAg-binding proteins we made use of a yeast two-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
1
1
0
Order By: Relevance
“…Interestingly, antigen-antibody binding on the rapid test was possible despite using denatured rL-HDAg. This is in agreement with previous studies which found that large segments of the HDAg protein sequence are intrinsically disordered but maintain the ability to form protein-protein interactions [33][34][35][36].…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, antigen-antibody binding on the rapid test was possible despite using denatured rL-HDAg. This is in agreement with previous studies which found that large segments of the HDAg protein sequence are intrinsically disordered but maintain the ability to form protein-protein interactions [33][34][35][36].…”
Section: Discussionsupporting
confidence: 93%
“…Myc-LAP1B and pET-LAP1B constructs have been previously described [15] . The pSIREN-RetroQ vector (Clontech) was kindly provided by Dr. Celso Cunha from the Instituto de Higiene e Medicina Tropical , Lisbon [17] . LAP1C was prepared by PCR amplification using the following primers: 5′-GAATTCATATGAAGACGCGAAGGAC-3′ and 5′-CTCGAGTTATAAGCAGATGCCCCT-3.…”
Section: Methodsmentioning
confidence: 99%